1992
DOI: 10.1088/0963-6625/1/4/002
|View full text |Cite
|
Sign up to set email alerts
|

Health and medical coverage in the UK national press

Abstract: The growth of UK public interest in health in the last decade is reflected by the inclusion in most national newspapers of regular health or medical sections. These potentially allow subjects to be covered in detail, with more background information and useful advice. This paper reports on a content analysis study of eight national newspapers, which aimed to obtain an overview of press health coverage, to compare the coverage of popular and quality papers, and to analyse differences in health topic coverage be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 11 publications
2
40
1
2
Order By: Relevance
“…Davidson and Wallack (2004, p.116) conclude that health reporting in the news is "...often superficial, confusing, or inaccurate", while previous research has highlighted a wide difference in reporting by the various genres of newspapers (Entwistle and Hancock-Beaulieu, 1992). The results from this study suggest articles on weaning in the tabloid and middle-market papers lacked a level of scientific detail and balance when compared to the quality newspapers.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Davidson and Wallack (2004, p.116) conclude that health reporting in the news is "...often superficial, confusing, or inaccurate", while previous research has highlighted a wide difference in reporting by the various genres of newspapers (Entwistle and Hancock-Beaulieu, 1992). The results from this study suggest articles on weaning in the tabloid and middle-market papers lacked a level of scientific detail and balance when compared to the quality newspapers.…”
Section: Discussionmentioning
confidence: 63%
“…Previous research has found that newspapers differ dramatically in their selection of topics and their narrative styles (Entwistle and Hancock-Beaulieu, 1992;Hilton et al, 2010 The use of personal testimonies was also favoured in newspapers such as the Daily Mail, suggesting the power and persuasiveness of including personal stories in the light of the public's mistrust of authority (Hilton et al, 2010).…”
Section: Newspaper Content Analysismentioning
confidence: 99%
“…This portrayal obscures the reality of diabetes as a disease which, although can indeed have very serious long-term biological consequences, people are able to manage successfully (Ellison and Rayman 1998), living full and long lives (Lutgers et al 2009). Thus the campaign mirrors the somewhat sensationalist way in which some quarters of the media report illnesses -with a strong focus on the debilitating and fatal aspects of disease at the expense of reporting how people actually live with and overcome the effects of illnesses (Entwistle and Hancock-Beaulieu 1992;Seale 2002: 45-47). One objection to our critical multimodal analysis is that if the campaign raises people's awareness of diabetes and prompts those at very real risk of the disease to act accordingly, then surely it is justified in harnessing a rhetoric of fear -the end, in other words, justifies the means.…”
Section: Discussionmentioning
confidence: 99%
“…In an expanding media universe, with escalating coverage of health and science issues (Clayton et al, 1993;Entwistle and Beaulieu-Hancock, 1992;Miller et al, 1998, pp. 147 Á8;Nelkin 1987), questions of who to trust to provide expert information and opinion is a vital issue for journalists and academics.…”
Section: Introductionmentioning
confidence: 99%